Catechol-O-methyltransferase inhibition with tolcapone reduces the "wearing off" phenomenon and levodopa requirements in fluctuating parkinsonian patients. Issue 4 (1st October 1997) - Baas, H; Beiske, A G; Ghika, J; Jackson, M; Oertel, W H; Poewe, W; Ransmayr, G
Abstract : BACKGROUND: More than 50% of patients with Parkinson's disease develop motor response fluctuations (the "wearing off" phenomenon) after more than five years of levodopa therapy. Inhibition of catechol-O-methyltransferase by tolcapone has been shown to increase levodopa bioavailability and plasma elimination half life, thereby prolonging the efficacy of levodopa. OBJECTIVES: The primary objective was to evaluate the efficacy of tolcapone in reducing "wearing off" in levodopa treated, fluctuating parkinsonian patients. Secondary objectives included assessment of reduction in levodopa requirements, improvement in patients' clinical status, duration of improvements, and tolerability of tolcapone. METHODS: In this multicentre, randomised, double blind, placebo controlled trial, 58 patients received placebo, 60 received 100 mg tolcapone three times daily (tid), and 59 received 200 mg tolcapone tid, in addition to levodopa/benserazide. RESULTS: After three months with 200 mg tolcapone tid, "off" time decreased by 26.2% of the baseline value, "on" time increased by 20.6% (P<0.01 v placebo), and the mean total daily levodopa dose decreased by 122 mg from the baseline dose of 676 mg (P<0.01). These responses were maintained up to nine months. With 100 mg tolcapone tid, "off" time decreased by 31.5% (P<0.05), "on" time increased by 21.3% (P<0.01), and the mean total daily levodopa dose decreased by 109 mg from the baseline dose of 668 mg (P<0.05). With 200 mg tolcapone tid, unified Parkinson's disease rating scale motor and total scores were significantly reduced, and quality of life (sickness impact profile) scores were significantly improved. Both dosages were well tolerated. Dyskinesia was the most often reported levodopa induced adverse event. Diarrhoea was the most often reported non-dopaminergic adverse event and the most frequent reason for withdrawal from the study: four patients in the 100 mg tolcapone tid group and six in the 200 mg tid group withdrew because of diarrhoea. CONCLUSION: Tolcapone prolongs "on" time in fluctuating parkinsonian patients while allowing a reduction in daily levodopa dosage, thereby improving the efficacy of long term levodopa therapy.